A comprehensive study on heat transfer enhancement in microchannel heat sink with secondary channel. (December 2018) - Japar, Wan Mohd Arif Aziz; Sidik, Nor Azwadi Che; Mat, Shabudin
Abstract: Microchannel heat sinks are used to remove high heat flux generated by electronic components. Microchannel heat sink has gained huge attention from former researchers due to its capability to enhance the heat transfer performance. However, the conventional design such as microchannel heat sink with rectangular channel becomes inadequate to remove very high heat flux due to thermal boundary layer thickness. In this paper, the effectiveness of secondary channel that implemented to the novel design which constructed by cavities and ribs are studied numerically for Reynolds number (Re) ranging from 100 to 450. The performance of proposed design (TC-RR-SC) is investigated by using a comparative analysis with related geometry such as microchannel with rectangular rib (CR-RR), microchannel with triangular cavity (TC) and microchannel with rectangular rib and triangular cavity (TC-RR). The result shows that TC-RR-SC design has an extraordinary overall performance compared to other designs due to combined effect of thermal boundary layer re-development and flow mixing in main channel. Besides that, the design shows the less flow and heat transfer irreversibility that contributed to thermal performance from the view of the second law of thermodynamics.